Theory and practice of natural computing : 6th International Conference, TPNC 2017, Prague, Czech Republic, December 18-20, 2017, Proceedings /: 6th International Conference, TPNC 2017, Prague, Czech Republic, December 18-20, 2017, Proceedings. (2017) - Unknown
No abstract available